RHINITIS ACCOMPANIED BY BILATERAL CONJUNCTIVITIS IN LOCAL CATS - I Nyoman Widya Putra Adnyana; I Gede Soma; I Nyoman Suartha (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Although cats are highly popular pets due to their high reproductive rates and good adaptability, many cat owners still neglect the necessary care for their pets, which can lead to the development of diseases. Therefore, it is important to thoroughly examine and correctly identify the diseases in cats so that appropriate treatment can be administered. The case involves a male cat named Lusi, aged 3 months, weighing 0.8 kg, a local breed with black and white fur, who has been reported to have sneezing and eye problems. A thorough physical examination was carried out, including pre-presence status and clinical assessment, focusing on the eyes and respiratory organs. Laboratory tests conducted included routine hematology, cytology of nasal and eye swabs, X-ray, Fluorescein Stain test, tonometry, and Rapid Antigen Test (Feline Calicivirus and Feline Herpesvirus). Clinical examination results showed mucopurulent discharge from the nose and both eyes, with conjunctival swelling and redness. Laboratory hematology results indicated anemia and leukocytosis, while cytological examination of the nasal and eye swabs revealed inflammatory neutrophil cells and bacteria. Fluorescein test, tonometry, and X-ray of the head and thoracic cavities were normal, and the antigen tests (Feline Calicivirus and Feline Herpesvirus) returned negative results. The cat was diagnosed with rhinitis accompanied by conjunctivitis with a favorable prognosis. This was supported by the anamnesis, clinical examination, and other supporting tests. The case was treated with antibiotics for seven days, resulting in improvement as the discharge and sneezing resolved. Owners are advised to pay more attention to maintaining a clean and healthy environment for their cats, as damp or dirty environments can foster the growth of bacteria and viruses that cause upper respiratory infections.